ORIGIN OF 1/F NOISE PEAKS OF YBA2CU3OX FILMS IN A MAGNETIC-FIELD - KANG, WN; KIM, DH; PARK, JH; HAHN, TS; CHOI, SS; GRAY, KE (ELSEVIER SCIENCE BV, 1994)
The temperature and magnetic-field dependence of 1/f noise from voltage fluctuations has been measured in epitaxial YBa2Cu3Ox films. In a magnetic field, two noise peaks were observed as temperature is reduced; one at higher temperature showed no magnetic-field dependence, while the peak near the zero-resistance transition temperature showed clear magnetic-field dependence. We show that the field-dependent noise is due to flux motion interacting with the pinning potential. A classical model is used to explain the flux-motion-induced noise peaks. The origin of the noise peaks is interpreted as due to the opposite temperature dependences of the flux-bundle size and the sample resistance. A rough estimate of the temperature and magnetic-field dependence of the flux-bundle size is presented.
Keywords: HIGH-TEMPERATURE SUPERCONDUCTORS; FLUX-FLOW NOISE; 1-F NOISE; RESISTANCE FLUCTUATIONS; RESISTIVE TRANSITION